Urgensi Ketahanan Nasional dan Bela Negara Bagi Bangsa Indonesia - Nopi Nopita Sari; Azhariah Fatya; Sinta Sinta; Bunga Sovia Erik; Amelia Rahmi; Siti Aisyah; Bambang Trisno (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
National resilience is one of the concepts of Indonesian statehood. The resilience of a nation is basically needed to guarantee and strengthen the capability of the nation concerned both in order to maintain its unity, face future threats and seek resources to meet life's needs. The research objective is to determine the urgency and challenges of national resilience and national defense for the Indonesian nation. Research results will be obtained using the Literature review research method, namely a method of collecting library data and information by exploring knowledge or knowledge from sources such as books, journals, written works, lecture notes and several other sources that are related to the research object. The research results show that resilience comes from the word "hold" which means steadfast, strong, able to control oneself, persistent, and never giving up. Resilience means being able, resistant and strong to face all forms of existing challenges and threats in order to ensure survival. Furthermore, according to Law no. 3 of 2002 concerning National Defense, citizens can physically participate in defending the country by becoming members of the Indonesian National Army and Basic Military Training. If the country's economic and financial conditions permit, the possibility of military service can also be considered. Defending the Country Non-Physically, namely: Participating in citizenship education through both formal and non-formal channels. Implementing a democratic life by respecting differences of opinion and not imposing one's will in solving common problems. Sincere devotion to the surrounding environment by planting, maintaining and preserving. Real work for humanity to advance the nation and state. Play an active role in overcoming threats, especially non-military threats, for example volunteering for flood disasters. Participating in spiritual mental activities among the community in order to ward off foreign cultural influences that are not in accordance with the norms of Indonesian life. Pay taxes and levies which function as a source of state financing to carry out development.